PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI PADA PEMERINTAH DAERAH KABUPATEN PANDEGLANG - Muhi Mukti; Ganjar Purna Galih (The Asia Pacific Journal Of Management Studies, 2020)
This study aims to determine and assess the effect of compensation on performance in the Regional Government (Pemda) of Pandeglang Regency. The research was conducted using quantitative methods. The study population was all employees in the Regional Government (Pemda) Pandeglang Regency as many as 12,333 people. The research sample is in the area of the Regional Government (Pemda) of Pandeglang Regency with 12,333 people. Data analysis uses descriptive-inferential analysis. The results showed that: (1) there was a significant relationship between compensation and employee performance in the Pandeglang District Government; (2) there is a significant effect of compensation on employee performance in the Pandeglang District Government; and (3) the magnitude of the effect of compensation on employee performance is 49.1%. The study concluded that there was a significant effect of compensation on employee performance in the Pandeglang District Government. Furthermore, further research is recommended with deeper and broader studies, both by adding research variables, expanding the scope of the research object, and using different methods.